2014
DOI: 10.1213/ane.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of Mitral Inflow Hemodynamics After Asymmetric Double-Orifice Repair

Abstract: The echocardiographic assessment of MV dysfunction after an Alfieri repair is important. Although the differences that we demonstrated between orifice areas and maximum velocities across the asymmetric orifices after a double-orifice MV repair are statistically significant, the corresponding difference in mean transorifice pressure gradient is not clinically relevant. Thus, either orifice can be interrogated with Doppler echocardiography for the determination of pressure gradients after double-orifice MV repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Trzcinka et al found that either orifice of a DOMV created by an Alfieri stitch could be used to obtain a gradient, even with asymmetric orifices, because the gradients should be similar. 13 Nevertheless, it should be noted that the interpretation of gradients through a mitral valve with an Alfieri stitch has been controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trzcinka et al found that either orifice of a DOMV created by an Alfieri stitch could be used to obtain a gradient, even with asymmetric orifices, because the gradients should be similar. 13 Nevertheless, it should be noted that the interpretation of gradients through a mitral valve with an Alfieri stitch has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…19 This creates 2 orifices that may be of equal or different sizes depending on the exact location of suture placement. 13 A DOMV may be more likely to be iatrogenic from an Alfieri stitch rather than congenital if (1) there is a normal mitral subvalvular apparatus, (2) there is a medical history of surgical intervention on the mitral valve, and (3) no additional congenital heart abnormalities are present. 7,20 As with the MitraClip, the Alfieri stitch seen with 3D TEE (Fig 3, B) lacks the well-defined ridge seen in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although velocities through the orifices may differ, the mean gradients should be similar. 9 A mean transvalvular gradient <5 mm Hg is the goal. The double orifice MVA should be measured by cumulative 3-dimensional planimetry because MVA by pressure half time has not been validated for a double orifice mitral valve.…”
Section: Therapies Targeting the Mitral Leafletmentioning
confidence: 99%